Relationships among athletic identity, mental health and social support in Japanese student-athletes during the COVID-19 pandemic - Hagiwara, G.; Tsunokawa, T.; Iwatsuki, T.; Shimozono, H.; Kawazura, T. (International Journal of Environmental Research and Public Health, 2021)
The purpose of this study was to investigate the relationships among student athlete`s identity and mental health during the COVID-19 pandemic. In addition, this study aimed to clarify the relationship between perceived social support from teammates and mental health in student-athletes. Two studies were conducted to investigate to clarify the mental health states of student-athletes in Japan during the COVID-19 pandemic. In Study 1 conducted in April 2020, the participants were 402 male student-athletes, and examined the relationships among student-athlete`s identity and mental health. The results of correlational analyses indicated that there were significant negative correlations between degree of student-athlete`s identity and depression and sports helplessness. In Study 2 conducted in March 2021, the participants were 136 male student-athletes, and examined the relationship between perceived social support from teammates, student-athlete`s identity and mental health. The results indicated that there was significant correlation among social support, student athlete`s identity and mental health. These results suggested that mental health may be improved if student-athletes are strongly aware of their social identity, which is their social role, when unforeseen events such as the COVID-19 pandemic occur. In addition, social support provided by significant others such as teammates may contribute to the improvement of mental health.